2001
DOI: 10.1152/ajpheart.2001.281.5.h1908
|View full text |Cite
|
Sign up to set email alerts
|

eNOS 894T allele and coronary blood flow at rest and during adenosine-induced hyperemia

Abstract: The 894T allele of a G894T polymorphism in the endothelial nitric oxide synthase (eNOS) gene is associated with decreased eNOS activity, cleavage of the protein, and endothelial dysfunction. The present study evaluated the association with coronary blood flow (CBF) at rest and during adenosine (ADO)-induced hyperemia. CBF was determined by Doppler flow wire and angiography in 97 left anterior descending arteries of individuals without coronary artery disease. At rest, average peak velocity (APV) was lower and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 23 publications
0
35
1
1
Order By: Relevance
“…57,58 Individuals homozygous for the Asp298 allele have also been shown to exhibit a reduced blood pressure fall after exercise training 61 and to have lower basal blood flow and reduced vasodilation to adenosine in their coronary arteries. 62 In addition, they have an enhanced systemic pressor response to phenylephrine 63 and a reduced flow-mediated dilatation of the brachial artery. 59 These findings suggest that subjects homozygous for the Asp298 allele generate low NO in vivo and may be more susceptible to endothelial dysfunction, which might account for the increased risk of IHD.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 Individuals homozygous for the Asp298 allele have also been shown to exhibit a reduced blood pressure fall after exercise training 61 and to have lower basal blood flow and reduced vasodilation to adenosine in their coronary arteries. 62 In addition, they have an enhanced systemic pressor response to phenylephrine 63 and a reduced flow-mediated dilatation of the brachial artery. 59 These findings suggest that subjects homozygous for the Asp298 allele generate low NO in vivo and may be more susceptible to endothelial dysfunction, which might account for the increased risk of IHD.…”
Section: Discussionmentioning
confidence: 99%
“…Among the identified eNOS polymorphisms, the G894T substitution within exon 7 resulting in the conversion of glutamate to aspartate at position 298 (Glu298Asp variant) is the one most frequently studied and has been reported to be associated with atherosclerotic coronary artery disease in two independent cohorts recruited from the Cambridge Heart AntiOxidant Studies (CHAOS-I and CHAOS-II). 13 The Glu298Asp variant was also reported to be associated with an enhanced systemic pressor response to phenylephrine in a French cohort, 14 a lower basal blood flow but a preserved response to adenosine in coronary arteries in Caucasians of German descent 15 and vasospastic angina pectoris in a Japanese population, 16 as well as with essential hypertension resistant to conventional antihypertensive therapy. 17 While these studies showed association of the Glu298Asp variant with atherosclerotic coronary artery disease, other studies do not support these findings.…”
Section: Enos Gene Expression In Atherosclerosis Enos Gene Polymorphimentioning
confidence: 98%
“…101 Although eNOS polymorphisms and altered coronary eNOS expression are associated with hypertension, 96,98,99 little direct evidence links mutations in the eNOS gene to specific mechanisms of coronary vascular dysfunction in hypertension. Certain polymorphisms for the 27 bp repeat at intron 4 and for the G894T have been associated with alterations in coronary vasomotor responses, 102,103 but this has not been assessed in a manner that allows for conclusions regarding the endothelium, or NO-dependency of the response. Thus, the precise mechanisms by which eNOS polymorphisms might affect coronary vascular function in hypertension have not yet been well established, and this important issue remains to be elucidated experimentally.…”
Section: Enos Polymorphisms Associated With Hypertension and Coronarymentioning
confidence: 99%